The Effect of Cash Ratio on Return on Asset (ROA) at PERUMDA BPR Garut - Eldiani, Nita; Lailasarry, Tania (Manunggal Halim Jaya, 2024)
The banking industry, especially rural banks (BPR), has a vital role in the local and national economy. This study aims to analyse the effect of Cash Ratio on Return On Assets (ROA) at Perumda BPR Garut. The method used is quantitative research with an associative approach, in which the relationship between variables is tested through regression analysis. The population of this study is the annual financial statements of Perumda BPR Garut for the period 2017-2023, with purposive sampling technique to select samples that meet certain criteria, namely financial reports that have been published during that period. This study used a sample of seven annual financial reports. The results showed that Cash Ratio had no significant effect on ROA. Although there is a weak relationship between the two variables, other factors, such as asset management and credit quality, affect bank performance more. The implication of this study is that it is important for the management of Perumda BPR Garut to pay attention to the management of other factors in increasing profitability, other than relying solely on liquidity ratios.